Anti-influenza triterpenoid saponins (saikosaponins) from the roots of Bupleurum marginatum var. stenophyllum. Issue 8 (15th April 2017) - Fang, Wei; Yang, Yin-Jun; Guo, Bao-Lin; Cen, Shan
Graphical abstract: Highlights: Fourteen saikosaponins including five novel ones were obtained. Nine saikosaponins showed potent inhibitory activity against H1N1. Three saikosaponins were promising anti-influenza agents. The preliminary structure-activity relationships were discussed. Abstract: This study to investigate antiviral components from the roots of Bupleurum marginatum var. stenophyllum led to the isolation of five novel saikosaponins, namely 6″-O- crotonyl- saikosaponin a (1 ), tibesaikosaponin I (2 ), tibesaikosaponin II (3 ), tibesaikosaponin III (4 ), tibesaikosaponin IV (5 ), along with 9 known analogues (6 –14 ). Their structures were established by spectral data analyses (IR, MS, 1D and 2D NMR) and by comparison of spectral data with those of the related known compounds. Antiviral testing of all compounds against influenza A virus A/WSN/33 (H1N1) in 293TGluc cells showed that nepasaikosaponin k (12 ), saikosaponin n (13 ) and saikosaponin h (14 ) behaved more potent inhibitory activity and selectivity than the positive control, Ribavirin. The preliminary structure-activity relationship studies suggest that the 13, 28-epoxy group, the type of sugar chain and the type of olefinic bonds are significant for antiviral activity and selectivity.